(untitled) (Mustansiria Dental Journal, 2024)
Purpose: to assess the erosive effect of antibiotic suspensions on the enamel of primary anterior teeth by using surface microhardness and scanning electron microscopy examination. Materials and method: The study utilized sixty anterior primary teeth. After preparation, the samples were divided into two groups, thirty samples each. The samples in group (1) were subjected to a suspension of amoxicillin. Samples in group (2) were subjected to the Cefixime suspension.Results: Significant differences were seen in enamel microhardness among the tested groups after the antibiotic syrup cycle. An independent sample T test was conducted to demonstrate that there were no significant differences in surface microhardness readings among the tested groups at the baseline of the study. While after three weeks of exposure to the antibiotic syrup, all groups experienced a decrease in enamel microhardness; the highest value was for Cefixime followed by Amoxicillin.Conclusion: Due to their acidity, antibiotics, which are frequently prescribed to youngsters, can erode primary enamel.